Plasma from chronic liver disease subjects exhibit differential ability to generate thrombin. Issue 7 (October 2015) - Yang, Zhineng J.; Sheth, Siddharth H.; Smith, Chad H.; Schmotzer, Amy R.; Lippello, Anita L.; Al-Khafaji, Ali; Chopra, Kapil B.; Smith, Roy E.
<x xml:space="preserve">Abstract</x> Liver fibrosis in chronic liver disease (CLD) results in complex alterations in procoagulant and anticoagulant proteins. Although an elevated international normalized ratio (INR) is a prominent feature of progressive fibrosis, the utility of the INR to accurately reflect the net effect of these changes on the coagulation system is uncertain. In subjects with CLD, elevated INRs have been observed in both bleeding and thrombotic complications, suggesting limitations of the INR in characterizing the coagulation status. Unlike the INR, which is preferentially sensitive to the extrinsic pathway, the direct measurement of thrombin generation better captures the global coagulation cascade. We conducted a pilot study measuring the INR, chromogenic factor X and thrombin generation in CLD subjects and compared them with control subjects and subjects on warfarin anticoagulation. We observed a large interquartile range in thrombin generation among compensated CLD subjects across a narrow INR range, suggesting that the INR is a suboptimal surrogate measure of thrombin generation in CLD subjects.